Masitinib for mild-to-moderate Alzheimer’s disease: results from a randomized, placebo-controlled, phase 3, clinical trial - Bruno Dubois; Jesús López-Arrieta; Stanley Lipschitz; Triantafyllos Doskas; Luiza Spiru; Svitlana Moroz; Olena Venger; Patrick Vermersch; Alain Moussy; Colin D. Mansfield; Olivier Hermine; Magda Tsolaki; et al. (Alzheimer’s Research & Therapy, 2023)
Abstract Background Masitinib is an orally administered tyrosine kinase inhibitor that targets activated cells of the neuroimmune system (mast cells and microglia). Study AB09004 evaluated masitinib as an adjunct to cholinesterase inhibitor and/or memantine in patients with mild-to-moderate dementia due to probable Alzheimer’s disease (AD). Methods Study AB09004 was a randomized, double-blind, two parallel-group (four-arm), placebo-controlled trial. Patients aged ≥50 years, with clinical diagnosis of mild-to-moderate probable AD and a Mini-Mental State Examination (MMSE) score of 12–25 were randomized (1:1) to receive masitinib 4.5 mg/kg/day (administered orally as two intakes) or placebo. A second, independent parallel group (distinct for statistical analysis and control arm), randomized patients (2:1) to masitinib at an initial dose of 4.5 mg/kg/day for 12 weeks that was then titrated to 6.0 mg/kg/day, or equivalent placebo. Multiple primary outcomes (each tested at a significance level of 2.5%) were least-squares mean change from baseline to week 24 in the Alzheimer’s Disease Assessment Scale - cognitive subscale (ADAS-cog), or the Alzheimer’s Disease Cooperative Study Activities of Daily Living Inventory scale (ADCS-ADL). Safety for each masitinib dose level was compared against a pooled placebo population. Results Masitinib (4.5 mg/kg/day) (n=182) showed significant benefit over placebo (n=176) according to the primary endpoint of ADAS-cog, −1.46 (95% CI [−2.46, −0.45]) (representing an overall improvement in cognition) versus 0.69 (95% CI [−0.36, 1.75]) (representing increased cognitive deterioration), respectively, with a significant between-group difference of −2.15 (97.5% CI [−3.48, −0.81]); p<0.001. For the ADCS-ADL primary endpoint, the between-group difference was 1.82 (97.5% CI [−0.15, 3.79]); p=0.038 (i.e., 1.01 (95% CI [−0.48, 2.50]) (representing an overall functional improvement) versus −0.81 (95% CI [−2.36, 0.74]) (representing increased functional deterioration), respectively). Safety was consistent with masitinib’s known profile (maculo-papular rash, neutropenia, hypoalbuminemia). Efficacy results from the independent parallel group of titrated masitinib 6.0 mg/kg/day versus placebo (n=186 and 91 patients, respectively) were inconclusive and no new safety signal was observed. Conclusions Masitinib (4.5 mg/kg/day) may benefit people with mild-to-moderate AD. A confirmatory study has been initiated to substantiate these data. Trial registration EudraCT: 2010-021218-50. ClinicalTrials.gov : NCT01872598